Solar chimney power plants : A review of the concepts, designs and performances - Cuce, Erdem; Cuce, Pinar Mert; Carlucci, Salvatore; Sen, Harun; Sudhakar, Kumarasamy; Md., Hasanuzzaman; Daneshazarian, Reza (MDPI, 2022)
This research presents a comprehensive review of solar chimney power plants (SCPP) as a reliable source of renewable electricity generation. Solar chimney power plants differ from other renewable energy technologies because thermal and momentum effects result in 24-h electricity generation. However, they are influenced by a wide range of design, geometrical and operational parameters, and environmental conditions. This review evaluates the design aspects and the theoretical, numerical, experimental, and performance findings in previous works holistically and concisely. The study also extensively discusses the various optimization strategies, advantages, disadvantages, and limitations of solar chimney power plants. Energy storage aspects and hybrid system designs are also addressed in the present review in order to overcome the known handicaps and limitations of solar chimney power plants. The performance figures of the technology are clearly demonstrated as a function of the design and operational conditions, and future prospects are discussed in detail. It is hoped that designers and policymakers will gain valuable insight into the technological features and advancements of solar chimney power plants, assisting them in making a better-informed decision.